MAKNA SLOGAN DALAM IKLAN ELEKTRONIK BERBAHASA INGGRIS PADA MAJALAH BERBAHASA INDONESIA - SUMILAT, JERNY LUCIANA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research entitled â€œMakna Slogan dalam Iklan Elektronik Berbahasa Inggris pada Majalah Berbahasa Indonesiaâ€, is focused on meaning of the mottoes or slogans in electronic advertisements. The aim of this research is to identify, analyze, and describe the types of meaning. The data are collected from several Indonesian magazines and in analyzing data, the writer uses theory from Leech (1974) about two types of meaning. The two types of meaning are conceptual (denotative) and associative meaning divided into six sub-types: connotative, social, affective, collocative, reflective, and thematic. The result of the research shows that the types of meaning of the sentence in the slogans contain conceptual (denotative) and associative meaning. The associative meaning include connotative and affective meaning. Â  Â  Keywords: slogan, advertisement, meaning, conceptual, associative